Two Mesolithic burials from Khor Shambat, Sudan - Maciej Jórdeczka; Łukasz Maurycy Stanaszek (Polish Archaeology in the Mediterranean)
The site of Khor Shambat 1 (KSH1) is located on the west bank of the Nile, in Omdurman, approximately 5 km north of Tuti Island. The first surveys there started in 2012, to be followed by an expedition of the Institute of Archaeology and Ethnology, Polish Academy of Sciences, which began four years later. A series of radiocarbon dates show that Mesolithic hunter-fisher-gatherers inhabited the site between 7000 and 5200 calBC, while Neolithic pastoralists settled there between 5000 and 3800 calBC. The research, carried out in nine trenches with a total area of nearly 180 m, yielded 66 human burials. While most of them were Neolithic and post-Meroitic, two graves found in the central part of the site contained remains of hunter-fisher-gatherers. The paper presents the results of archaeological, anthropological, and bioarchaeological research on the skeletons of the two Mesolithic men. The analyses are presented against a broader background of Early Holocene settlement in Central Sudan.